2016
DOI: 10.18632/oncotarget.9373
|View full text |Cite
|
Sign up to set email alerts
|

Paclitaxel is necessary for improved survival in epithelial ovarian cancers with homologous recombination gene mutations

Abstract: PURPOSETo investigate the impact of somatic mutations in homologous recombination (HR) genes on the chemotherapeutic response and survival of patients with epithelial ovarian cancer (EOC).EXPERIMENTAL DESIGNWe performed targeted massively parallel sequencing of tumor DNA from 158 patients with EOC. We associated adjuvant chemotherapy and clinical outcome with mutations in selected genes, focusing on those encoding HR proteins.RESULTSHR mutations were found in 47 (30%) tumors. We did not detect an overall survi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Pre-clinical and translational studies have found links between TP53 loss of function and resistance to DNA damaging agents like platinum compounds and anthracyclines [16]. Conversely, tumors with loss of normal TP53 function may be even more sensitive to anti-cancer agents like Paclitaxel that stabilizes tubulin polymerization resulting in the arrest of mitosis and the induction of TP53-independent apoptosis [23,24]. It has been also demonstrated that Paclitaxel, especially in fractionated regimens, exploits anti-angiogenic mechanisms of action [25] Together, these chemotherapy-related aspects, in addition to pre-clinical and clinical studies linking TP53 mutations to the VEGF pathway [5][6][7][8] and anti-VEGF/VEGFR systemic therapies [9][10][11][12][13][14][15], contribute to explaining the favorable results of the Ramucirumab/Paclitaxel combination in metastatic gastric cancers harboring TP53 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Pre-clinical and translational studies have found links between TP53 loss of function and resistance to DNA damaging agents like platinum compounds and anthracyclines [16]. Conversely, tumors with loss of normal TP53 function may be even more sensitive to anti-cancer agents like Paclitaxel that stabilizes tubulin polymerization resulting in the arrest of mitosis and the induction of TP53-independent apoptosis [23,24]. It has been also demonstrated that Paclitaxel, especially in fractionated regimens, exploits anti-angiogenic mechanisms of action [25] Together, these chemotherapy-related aspects, in addition to pre-clinical and clinical studies linking TP53 mutations to the VEGF pathway [5][6][7][8] and anti-VEGF/VEGFR systemic therapies [9][10][11][12][13][14][15], contribute to explaining the favorable results of the Ramucirumab/Paclitaxel combination in metastatic gastric cancers harboring TP53 mutations.…”
Section: Discussionmentioning
confidence: 99%
“…The biological effects resulted from up-regulated ABCB1 expression in the patients undergoing taxane-containing therapy might be compensated by other mechanisms that need further investigation. On one hand, it seemed that extensive use of taxanes successfully improved the general survival of EOC patients comparing to other drugs [69] and attenuated the sensitivity of ABCB1 as a prognosis indicator. On the other, since both cellular and clinical researches revealed that ABCB1 in ovarian cancer could be up-regulated by chemotherapy [70, 71], taxane induced alteration in ABCB1 through the course of treatment might also be a confounding factor to the measurement of survival analysis because ABCB1 expression was seldom obtained in matched analysis [7274].…”
Section: Discussionmentioning
confidence: 99%
“…The OV01 clinical trial evaluation further indicated that a high level of CIN could contribute to taxane resistance, suggesting CIN may serve as a predictor for response to taxane treatment [58]. A retrospective cohort study showed that the combined use of paclitaxel could benefit the survival of patients with homologous recombination (HR)-deficient ovarian cancers [60]. On the other hand, paclitaxel can inhibit the overexpression of nucleotide excision repair (NER)-related genes induced by doxorubicin, thereby improving the efficacy of the dose-dense ACT protocol for breast cancer treatment [61].…”
Section: Dna Damage and Dna Repair Inhibitionmentioning
confidence: 99%